Three-dimensional local anisotropy of velocity fluctuations in the solar wind. Issue 3 (13th April 2019) - Verdini, Andrea; Grappin, R; Alexandrova, O; Franci, L; Landi, S; Matteini, L; Papini, E
Abstract: We analyse velocity fluctuations in the solar wind at magneto-fluid scales in two data sets, extracted from Wind data in the period 2005–2015, that are characterized by strong or weak expansion. Expansion affects measurements of anisotropy because it breaks axisymmetry around the mean magnetic field. Indeed, the small-scale three-dimensional local anisotropy of magnetic fluctuations (δ B ) as measured by structure functions ( SFB ) is consistent with tube-like structures for strong expansion. When passing to weak expansion, structures become ribbon-like because of the flattening of SFB along one of the two perpendicular directions. The power-law index that is consistent with a spectral slope −5/3 for strong expansion now becomes closer to −3/2. This index is also characteristic of velocity fluctuations in the solar wind. We study velocity fluctuations (δ V ) to understand if the anisotropy of their structure functions ( SFV ) also changes with the strength of expansion and if the difference with the magnetic spectral index is washed out once anisotropy is accounted for. We find that SFV is generally flatter than SFB . When expansion passes from strong to weak, a further flattening of the perpendicular SFV occurs and the small-scale anisotropy switches from tube-like to ribbon-like structures. These two types of anisotropy, common to SFV and SFB, are associated with distinct large-scale variance anisotropies of δ B in the strong- and weak-expansion data sets. We conclude that SFV show anisotropic three-dimensional scaling similar to SFB, with however systematic flatter scalings, reflecting the difference between global spectral slopes.